Cultivation of Oyster Mushroom could be a Viable Option for Doubling the Farmer’s Income - An Overview - Chauhan, Anita; Negi, Shivangi; Kaur, Rupinder; Chauhan, Manish; Dhanai, Rekha; Negi, Pankaj Singh (International Journal of Economic Plants, 2024)
Our country is celebrating 75th year of Azadi ka Amrit Mahotsava and our Government is very much focused on how to double the farmer’s income, it is the utmost duty of every researcher, educationist and agriculture scientist to explore the ways and means to achieve this target. The cultivation of oyster mushrooms has the potential to significantly increase the income of farmers. Oyster mushrooms are easy to grow, require minimal resources, and have a high market demand. By cultivating oyster mushrooms, farmers can diversify their income streams and increase their profits. This abstract suggests that oyster mushroom cultivation could be a viable option for farmers looking to double their income. Indian economy is primarily agriculture based and where the average income from Agriculture Sector ha-1 is very less in comparison to the other developed nations of the world. This is a call of time to enhance the farmer’s income so they can live their lives in a lucrative manner. Present objective cannot be achieved merely by enhancing the price of the different agricultural produce which the farmers grow on their farm lands, but we should include certain other practical implications to increase the existing productivity level of different agricultural and allied ventures by diversifying farm enterprises. Mushroom culture is one of such enterprises with particular reference to oyster mushroom which has the vast potential to double the existing income level of farmers and this enterprise can easily be adopted by any category of farmers even having marginal landholding.